Analysis of SENAR's ATeG in dairy properties in the Tijuco river basin in Uberlândia (Revista Brasileira Multidisciplinar, 2025)
The aim of this study was to analyze whether the goals of the Technical and Managerial Assistance (ATeG) methodology were achieved and the impacts of the program on dairy producers assisted in the Tijuco River Basin in Uberlândia/MG. A bibliographic-documentary research method was used, allowing the collection of primary information obtained from the Technical and Managerial Assistance Management System (SISATEG). This information was organized into two categories of analysis: Productive Indicators and Economic Indicators. According to the results, it was observed that there was no significant change in the productive indicators during the period, following a market trend where there was a reduction in the values found in properties assisted by ATeG, similar to the reduction occurring in properties in Minas Gerais and Brazil as a whole. However, the analysis of economic indicators shows that there was more assertive and balanced managerial control by the dairy properties assisted by ATeG. Even in a period of extreme concern for the sector, with rising input prices and all production costs, the properties assisted by the program achieved significant improvements in gross margin, net margin, and profit per liter of milk produced. According to the evaluation of the producers themselves, the assistance provided by ATeG is rated in the excellence zone according to the Net Promoter Score (NPS) satisfaction assessment methodology.
Keywords: Technical and managerial assistance; SENAR; Productive indicators; Economic indicators; Management